Current methods of non-invasive diagnostics of skin melanoma - N. P. Malishevskaya; A. V. Sokolova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Malignant skin neoplasms including melanoma are now occupying the leading positions in the list of cancer pathologies in Russia, a number of European countries and United States. The percentage of melanoma is less than 4% of the total number of skin neoplasms but melanomas account for up to 80% of lethal cases caused by malignant skin neoplasms. Due to the aggressive nature of melanomas including the proliferative reaction to any invasions including diagnostic ones, there is an urgent need in a reliable non-invasive method to differentiate melanomas from other skin neoplasms and diagnose it at an early stage. This review article discloses descriptions, potential, advantages and shortcomings of non-invasive melanoma diagnostics methods: dermatoscopy, SIAscopy and confocal microscopy. Based on the results of the review, the authors made a conclusion that the development of an algorithm of diagnostics taking into account individual clinical and medical history data, results of non-invasive visualization methods and laboratory test results (proteome analysis, tumor markers) would help to overcome the shortcomings of each individual method, diagnose melanomas at early stages and, respectively, personalize the approach to management for each patient.